Hydrographic data from the Rio Grande Cone region, southwestern Atlantic Ocean in 2024 - Rafael A Avila; Jose H Muelbert (PANGAEA, 2025)
This dataset contains nine vertical profiles of temperature, potential temperature, conductivity, salinity, pressure, potential density, fluorescence, and dissolved oxygen. All data were obtained during the TRIATLAS III cruise, carried out from Jun 7 to 9, 2024, in the area of the Rio Grande Cone, an important region in the southwestern Atlantic Ocean regarding sediment transport, biological production, and mesoscale circulation. The cruise goal was to investigate the behavior and abundance of mesopelagic fauna in the Rio Grande Cone region and the potential of this region to be a hot spot for biological production. All data were obtained with a SeaBird SBE 19Plus V2 SeaCat Profiler CTD (conductivity, temperature, and depth) and are properly treated by the manufacturer-provided software.